Should wealth transfers be taxed? Citizens' view on a fundamental question - Ivo Bischoff; Nataliya Kusa (Philipps-University Marburg, School of Business and Economics, 2016)
In a recent representative survey, German citizens are asked whether or not inherited wealth beyond a certain amount should be taxed. Almost 60 percent stated that it should not be taxed. We use this survey to identify the factors that drive this fundamental opposition against the taxation of inherited wealth. We find monetary self-interest and redistributive preferences to drive citizens' attitude in this matter. We account for other intra-familial transfers, in partic-ular long-term care. Being at the heart of intra-familial exchange relations, women are more likely to oppose wealth transfer taxation than men are. Citizens' attitude towards inheritance taxation does not depend on their personal experience in giving long-term care. Expecting the typical German family to reward intra-familial caregiving through a higher inheritance reduces the opposition against the taxation of inherited wealth.
Keywords: H27; D31; D72; 330; inheritance taxation; intergenerational transfers; citizens' preferences; long-term care; vignettes